Aplicación del presupuesto participativo y su impacto en el GAD Municipal del Cantón San Miguel de Bolívar. - Barahona Manzano, Marcia del Lourdes (2016)
This research analyzes the implementation of participatory budgeting in the GAD San Miguel, searching into its features, limitations and reaches, based on them to develop a proposal to improve the system of participatory budgeting and the life of the community from San Miguel. In the first chapter this paper describes the characteristics of the participatory budget, its key components, the relationship of local development and meaningful experiences are discussed concerning the successful implementation of participatory budgeting. In second chapter the research area is delimited, methodologies and tools, based on several proposed formats to monitor and follow up the participatory budget process are defined. The third chapter presents the results obtained and systematized both interviews and surveys, so finally in the fourth chapter develop a proposal to improve the implementation of participatory budgeting and social impact.